Epidemia de sarampo e trabalho escravo no Grão-Pará (1748-1778) - VIEIRA JUNIOR, Antonio Otaviano (Universidade Federal do Pará, 2017)
The paper discusses the population impact of the measles epidemic (1748-1750) in Grão-Pará (a captaincy of the Portuguese Empire, now northern Brazil) and its relation to the process of insertion of African slave labor. The analysis is based on the documentation produced in the 18th century, including official correspondence, essays, memoirs, population maps and lists of those killed by the epidemic. The serial documentation was entered into a database, created from 80 lists of those killed by measles, which allowed an analysis of the demographic impact of the disease. Concomitantly, the population count of the captaincy’s towns and villages from the third quarter of the 18th century composed a second database and facilitated understanding of the internal distribution of African slaves. The point of intersection between the databases is the set of historical administrative documents, which addresses the effects of the epidemic and the possible solutions to the labor crisis - caused by the high mortality of indigenous peoples. The study shows not just measles mortality, but also the construction of a policy for the insertion of African slaves in the region. As such, the text is divided into two parts: the first deals with the epidemic itself, its presence in the city Belém, the importance of indigenous labor for the colonists, the number of deaths and the distribution of mortality in terms of space and seasonality (months and years). The second part discusses the fundamental struggle between projects that addressed the demand for labor, the policy of insertion of African slaves as a means to combat the high mortality of measles, and the distribution of these slaves in the captaincy.